Dinâmica agrária, instituições e governança territorial para o desenvolvimento sustentável da Amazônia - COSTA, Francisco de Assis (Universidade Federal do Pará, 2018)
Referring to the Institutionalist debate in economics, the article discusses institutional arrangements in the Amazon taking into account the structural diversity that characterizes the rural sector in the region. Based on the different patterns of relationships between technological trajectories, two large representative configurations of development conditions are established: i) rural economies based on agriculture and livestock, and ii) economies based on agroforestry systems. Comparing the results of agricultural censuses of 1995 and 2006 one finds, for each case, structural changes in the period and speed, fundamentals and impacts of growth are analyzed. Special attention is given to the institutional foundations of the processes. As a result, two large institutional arrangements are presented, one that has the “land market”, and another that has the rules of access to common resources of biomes and ecosystems as its core foundation. Formal institutional mechanisms operate in each territory and interact with these informal institutions, and that characterizes the prevailing territorial governance. As a conclusion, it is found that a practical implication of it is that development policies based on sustainability should seriously consider these distinctions.